Respuesta :
NO. You cannot subtract 3x from 6, since they are NOT like terms.
You can think of it as the 6 does not have an x term, but in 3x, there is an x term.
You can think of it as the 6 does not have an x term, but in 3x, there is an x term.
Answer: When "x = 1" ; "2(6-3x) + x" DOES EQUAL "2(3x) + x" .
___________________________________________________
2(6-3x) + x = 12 - 6x + x = 12 - 5x ;
2(3x) + x = 6x + x = 7x ;
Does: 12 - 5x = 7x ?
Add "5x" to each side of equation:
12 - 5x + 5x = 7x + 5x ;
to get:
12 = 7x + 5x ;
12 = 12x ;
Divide each side of the equation by "12" ;
12 / 12 = 12x / 12 ;
to get: 1 = x ; ↔ x= 1 ;
_______________________________________
Answer: "When "x = 1" ; "2(6-3x) + x" DOES EQUAL "2(3x) + x" .
___________________________________________________
___________________________________________________
2(6-3x) + x = 12 - 6x + x = 12 - 5x ;
2(3x) + x = 6x + x = 7x ;
Does: 12 - 5x = 7x ?
Add "5x" to each side of equation:
12 - 5x + 5x = 7x + 5x ;
to get:
12 = 7x + 5x ;
12 = 12x ;
Divide each side of the equation by "12" ;
12 / 12 = 12x / 12 ;
to get: 1 = x ; ↔ x= 1 ;
_______________________________________
Answer: "When "x = 1" ; "2(6-3x) + x" DOES EQUAL "2(3x) + x" .
___________________________________________________